Associated factors with service utilization goals in municipalities of Bahia with Dental Specialty Centers from 2013-2019 (Research, Society and Development, 2021)
Objective: To identify the factors associated with the achievement of the goal of utilization of dental services in primary care and specialized care of the municipalities with a CEO in the state of Bahia, from 2013 to 2019. Methodology: This is a cross-sectional, exploratory and analytical study, using secondary data obtained from the Outpatient Information System, the WEB platform e-Gestor Basic Care, the Information System on Public Health Budgets and the 1st cycle of the National Program for Improving Access and Quality of Dental Specialty Centers. We analyzed 73 municipalities in Bahia with an implemented oral health team and with the CEO, through the utilization indicators proposed for oral health by the Ministry of Health. The variables were related to demographic characteristics, financing and supply of services, and the response variable was compliance with 50% of two standards of the ordinance Nº 1.631 de 1 de october de 2015. Results: In the final sample, 58.90% of the municipalities were small, 50.68% showed above 85.9% participation of intergovernmental transfers in total revenue, 49.32% had oral health coverage in primary care above 77.7% and 43.83% had CEO type I. There was statistical significance in the association between oral health coverage and achievement of 50% or more of the goal. Conclusion: It was evidenced that smaller municipalities, with participation of intergovernmental transfers in total revenues above 85.9%, with oral health coverage above 77% and with a type I CEO, achieved greater compliance with the goal. It is concluded that low oral health coverage contributes to the noncompliance of 50% of the goal.